Pengembangan Alat Pemorsian Nasi Sesuai Standar Diet Pasien Rawat Inap di Rumah Sakit - Iswanelly Mourbas; Mulyatni Nizar; Gusnedi Gusnedi (Poltekkes Kemenkes Padang, 2020)
Background: Inaccuracy of rice portions for diets is related to the use of non-standard portioning tools. Objectives: This study aimed to develop a standardized rice portioning device for hospitalized inpatients. Methods: The process of tool design used AutoCAD software with three-dimensional parameter input that was equivalent to a portion of 150g, 200g, and 250g of steam rice. The tools were printed using a 3D printer with a food-safe Polylactic Acid filament as the base material. The accuracy of the portioning tools was measured by weighing and comparing the weight of the rice served with the hospital's standard portion. Results and conclusions: The portioning tools (150g, 200g, and 250g) have the same diameter of the base (54 mm), the surface diameters (mm) are 105.5; 105.0, 103.4, respectively; and the heights (mm) are 37; 51; and 65 respectively. The portioning devices have very good accuracy (99.2% - 100.3%) of the standard hospital portion, much better than the tools commonly used by hospitals (72-129%). They are also easy to use, easy to clean, light, and durable. Recommendation: It is recommended that the hospital use the tools for a more accurate rice portion and in accordance with established dietary standards.